Study of Sustainable Gastronomy Tourism in Siantar City - Maleachi, Sandra; Juliana, Juliana; Sianipar, Rosianna; Sitorus, Nova Bernedeta (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to identify the sustainability of gastronomic tourism in Siantar City. The